Properties of spatial arrangement of V-type defects in irradiated materials: 3D-modelling - Kharchenko, V.O.; Kharchenko, D.O. (Condensed Matter Physics, 2013)
We consider the dynamics of pattern formation in a system of point defects under sustained irradiation within the framework of the rate theory. In our study we generalize the standard approach taking into account a production of defects by elastic fields and a stochastic production representing internal multiplicative noise. Using 3D-modelling we have shown that with the damage rate growth, a morphology of clusters composed of vacancies changes. The same effect is observed with variation in the multiplicative noise intensity. Stationary patterns are studied by means of correlation analysis. Проведено дослiдження динамiки структуроутворення в системi точкових дефектiв при сталiй дiї опромiнення в рамках швидкiсної теорiї. Нами узагальнено стандартний пiдхiд врахуванням впливу пружних полiв та стохастичного виробництва дефектiв, що представляється внутрiшнiм мультиплiкативним шумом. В рамках застосування процедури 3D-моделювання встановлено, що зростання швидкостi набору дози приводить до змiни морфологiї структур, якi складаються з вакансiй. Аналогiчний ефект спостерiгається при варiюваннi iнтенсивностi мультиплiкативного шуму. Стацiонарнi структури дефектiв дослiджено iз застосуванням кореляцiйного аналiзу.